Examining Rural Maternal Gender Attitudes Over Time: Will she Belong to Another Family, Anyway? - Kong, Peggy; Zhang, Yuping (Australian and International Journal of Rural Education, 2018)
Over the last 60 years, egalitarian gender roles have been a prominent component of China’s development plan. With changing social and economic policies, there is growing research in both urban and rural areas that suggests the weakening of traditional gender values. But, little research has been focused on examining the change of gender attitudes over time. Using Bourdieu’s concept of cultural capital, this paper explores how maternal gender attitudes change over time and also the relationship between maternal gender attitudes and subsequent educational attainment for girls and boys. Drawing from the Gansu Survey of Children and Families (GSCF), a longitudinal survey of parents, teachers, children, principals, and village heads, we compare maternal perceptions of girls and boys in 2000 and 2004 and their children’s educational attainment in 2009. Much of the literature in rural China suggests that traditional gender attitudes are static and reinforce traditional gender norms. Our findings suggest that maternal gender attitudes are not fixed and change over time. We find that maternal gender attitudes are not uniform and that there is a relationship between mothers who hold egalitarian gender attitudes and positive educational outcomes for girls.